Peer Tutoring System in Improving Science Learning Achievement at Madrasah Ibtidaiyah: Sistem Bimbingan Teman Sebaya dalam Meningkatkan Prestasi Belajar Ilmu Pengetahuan di Madrasah Ibtidaiyah - Siswanto, Siswanto; Romadlon, Dzulfikar Akbar (Indonesian Journal of Islamic Studies, 2025)
General Background: Education quality at the elementary level plays a crucial role in developing students’ academic achievement. Specific Background: In Madrasah Ibtidaiyah, the learning outcomes in science subjects remain suboptimal despite various instructional methods. Knowledge Gap: Previous studies have examined peer tutoring in mathematics and physical education, but limited research has focused on its application in science learning at the Islamic elementary level. Aims: This study aims to determine the effectiveness of the peer tutoring learning system in improving students’ science achievement. Results: Using a quasi-experimental design with control and experimental groups, the findings revealed a significant increase in students’ post-test scores in the experimental group, supported by t-test analysis. Novelty: The study contributes by demonstrating the practical integration of peer tutoring in Islamic school contexts. Implications: The results suggest that peer tutoring fosters collaboration, motivation, and deeper understanding among students in science learning. Highlights:• Peer tutoring effectively enhances students’ science learning outcomes.• The quasi-experimental design confirms significant performance differences.• Peer-based learning fosters motivation and social interaction. Keywords: Peer Tutoring, Learning Achievement, Science Education, Madrasah Ibtidaiyah, Collaborative Learning